An Analysis of PT.X (Yogyakarta)'s Development Cycle Based on Adizes and Galbraith's Theories - Andreas Fajar Nugroho (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
E-commerce is a business strategy that promotes products and services through digital marketing platforms, one of which is PT.X. PT.X operates in multiple countries, including Indonesia, specifically in Yogyakarta. The Yogyakarta branch of PT.X consistently meets its annual targets and tends to express satisfaction with these achievements, often overlooking the crucial role of employee efficiency in reaching these goals. This study aims to explore the background and organizational culture of PT.X, assess its developmental stage based on the models of Adizes and Galbraith, and examine the challenges and strategies needed to sustain its current development stage. The organizational culture of PT.X (Yogyakarta) has been analyzed using the Organizational Culture Assessment Instrument (OCAI), revealing that the most significant desired cultural change is a reduction in Hierarchy culture by 7.50 points and a notable increase in Adhocracy culture by 6.83 points. According to Ichak Adizes, PT.X is currently in the 'Stable Organization' phase of its development cycle. Meanwhile, Jay Galbraith’s Star Model suggests that PT.X (Yogyakarta) could undergo significant transformation by focusing on the areas of organizational structure and human resources—particularly addressing the issue of high employee turnover. Based on Adizes' (2014) model, PT.X (Yogyakarta) has reached the stability stage in its organizational life cycle. At this point, it is crucial to pay attention to potential factors that may lead to stagnation or organizational decline. As Galbraith (2014) emphasizes, sustaining organizational development requires addressing existing constraints—such as those currently faced by PT.X (Yogyakarta).